2008
DOI: 10.1056/nejmoa0707330
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Inhibition and Renal Thrombotic Microangiopathy

Abstract: The glomerular microvasculature is particularly susceptible to injury in thrombotic microangiopathy, but the mechanisms by which this occurs are unclear. We report the cases of six patients who were treated with bevacizumab, a humanized monoclonal antibody against vascular endothelial growth factor (VEGF), in whom glomerular disease characteristic of thrombotic microangiopathy developed. To show that local reduction of VEGF within the kidney is sufficient to trigger the pathogenesis of thrombotic microangiopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
1,079
12
22

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,373 publications
(1,153 citation statements)
references
References 19 publications
40
1,079
12
22
Order By: Relevance
“…It is interesting therefore that genetic deletion of vascular endothelial growth factor in podocytes only, is sufficient to trigger endothelial death and severe thrombotic glomerular injury. 49 Our studies confirmed the existence of a cell defined as fibrocyte, which did not express ␣SMA. Although we detected fibrocytes in injured kidney, spleen, and BM they were not detected in the circulation, suggesting that fibrocytes differentiate locally into coll1a1ϩ cells from either pre-existing cells or from circulating leukocytes such as a monocyte.…”
Section: Discussionsupporting
confidence: 77%
“…It is interesting therefore that genetic deletion of vascular endothelial growth factor in podocytes only, is sufficient to trigger endothelial death and severe thrombotic glomerular injury. 49 Our studies confirmed the existence of a cell defined as fibrocyte, which did not express ␣SMA. Although we detected fibrocytes in injured kidney, spleen, and BM they were not detected in the circulation, suggesting that fibrocytes differentiate locally into coll1a1ϩ cells from either pre-existing cells or from circulating leukocytes such as a monocyte.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to the de novo identified podocyte-specific genes, genes that have been shown by genetic or functional studies to be causally involved in hereditary glomerular diseases and chronic progressive renal failure, including DACH1 (nanodissection rank 184) (Köttgen et al 2010), APOL1 (rank 185) (Genovese et al 2010;Kopp et al 2011), VEGFA (rank 247) (Eremina et al 2008;Köttgen et al 2010), and MYH9 (rank 260) (Kao et al 2008;Kopp et al 2008), were ranked highly by our method. During the preparation of this manuscript, MYO1E (rank 75) was reported to be associated with autosomal-recessive, glucocorticoid-resistant nephrotic syndrome (Mele et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of VEGF or its receptors has been shown to lead to vessel regression in a number of tissues. In the kidney, VEGF neutralization resulted in glomerular endotheliosis and proteinuria (5)(6)(7). Vessel regression was also noted in the pancreas (8,9), trachea, thyroid, and small intestine (8).…”
mentioning
confidence: 99%